Quality of life in rectal cancer patients with or without oxaliplatin in the randomised CAO/ARO/AIO-04 phase 3 trial - Kosmala, Rebekka; Fokas, Emmanouil; Flentje, Michael; Sauer, Rolf; Liersch, Torsten; Graeven, Ullrich; Fietkau, Rainer; Hohenberger, Werner; Arnold, Dirk; Hofheinz, Ralf-Dieter; Ghadimi, Michael; Ströbel, Philipp; et al. (European journal of cancer, 2021)
Background - The CAO/ARO/AIO trial has shown that oxaliplatin added to preoperative chemoradiotherapy and postoperative chemotherapy significantly improved disease-free survival in locally advanced rectal cancer (LARC). Here, we present a post-hoc analysis of quality of life (QoL) in disease-free patients. - Patients and methods - Between 2006 and 2010, 1236 patients with LARC were randomly assigned either to preoperative chemoradiotherapy followed by total mesorectal excision and postoperative chemotherapy (N = 623) or combined with oxaliplatin (N = 613). QoL questionnaires (EORTC QLQ-C30, colorectal module CR38) were completed at baseline, after postoperative chemotherapy and during follow-up. Analysis was performed according intent-to-treat. - Results - Available questionnaires (baseline) were 82% (N = 512) in the control and 84% (N = 513) in the investigational group. Response rates were 49% (533 of 1086) at 1 year and 43% (403 of 928) at 3 years. Global health status (GHS) for disease-free patients was stable in both groups (range 0-100). At baseline: standard arm 62.0 (mean, SD 21.6; N = 491) versus oxaliplatin arm 63.2 (mean, SD 22; N = 503); at 3 years: 69.4 (SD 19.3; N = 187) versus 65.4 (SD 22.2; N = 202). After treatment and at 3 years, no significant differences (≥10 points) between groups were found in QoL subscales. Disease-free patients experiencing neurotoxic side-effects (grade 1-4) showed reduced GHS at 3 years versus patients without neurotoxicity (mean 59.2 versus 69.3; P < 0.001), while grade 3-4 rate was low. - Conclusion - The addition of oxaliplatin was not associated with worse overall QoL. This information is of interest to patients in many ongoing rectal cancer trials. - Trial registration information - NCT00349076.
Gesehen am 14.04.2021